Impact of a Novel Oblique-Tip Papillotome for Biliary Cannulation during ERCP: A Nonrandomized Coarsened Exact Matching Study. (7th May 2020) - Imazu, Hiroo; Ho, Shiaw-Hooi; Hino, Shoryoku; Goh, Khean-Lee; Moriyama, Mitsuhiko; Sumiyama, Kazuki; Tajiri, Hisao
Abstract : Background . We developed a novel oblique-tip papillotome (OT-papillotome) to facilitate biliary cannulation during endoscopic retrograde cholangiopancreatography (ERCP). This study was performed to evaluate the utility of the OT-papillotome for contrast-guided cannulation (CGC) and wire-guided cannulation (WGC) during ERCP, compared with standard cannulation by WGC using a standard-tip papillotome (ST-papillotome). Methods . A prospective study was performed at two centers. CGC with the OT-papillotome (OT-CGC group) was performed at Jikei University Hospital, while WGC was done with the OT-papillotome and ST-papillotome (OT-WGC and ST-WGC groups, respectively) at the University of Malaya Medical Centre. The results of the OT-CGC and OT-WGC groups were compared with those of the ST-WGC group after performing coarsened exact matching (CEM) to reduce bias due to nonrandomized and center-based patient allocation. Results . Eighty patients were enrolled in each of the OT-CGC, OT-WGC, and ST-WGC groups. After CEM, the successful biliary cannulation rate was significantly higher in the OT-CGC and OT-WGC groups than in the ST-WGC group, while rescue cannulation was reduced. The mean number of unintended pancreatic access events in the OT-WGC and OT-CGC groups was similar to the ST-WGC group. However, it was significantly lower in the OT-WGC group than in the OT-CGC group. Multivariate analysis revealed that the OT-papillotome was independently associated with less frequent rescue cannulation and a higher successful biliary cannulation rate. Conclusions . Although use of the OT-papillotome in biliary cannulation did not reduce unintended pancreatic access events or PEP compared to the ST-papillotome, the OT-papillotome increased the successful biliary cannulation rate, while reducing the frequency of rescue cannulation procedures. Combining the OT-papillotome with WGC might be the best cannulation technique for minimizing unintended pancreatic access.